The founding of Marxist study of religion and its theoretical sources of humanities - Chuanhui Zeng; Xiaoxiao Zhang (HTS Teologiese Studies/Theological Studies)
Marx and Engels have elaborated the new system of their thought in German Ideology, including some important ideas on religion, from 1845 to 1846. Engels firstly applied the newly founded worldview and methodology to the systematic study of religion in his monograph Peasant War in Germany in 1850. Both events marked the founding of the Marxist Study of Religion. The Marxist humanity theory of religion benefitted from the religious critiques of Neo-Hegelian, Feuerbachian and religious philosophy. The social theoretical sources of Marxism on religion are supposed to be the topics of other articles.